Number 39 (November 1999) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1999)
(November 1999) - Instantaneous growth and mortality of alevin channel catfish Ictalurus punctatus (Siluriformes: Ictaluridae) in the Oconee River, Georgia. By Carl R. Ruetz III and Cecil A. Jennings Fish richness and abundance in created riparian habitats of channelized northern Mississippi streams. By Peter C. Smiley Jr., Scott S. Knight, Charles M. Cooper and Kenneth W. Kallies
Keywords: alevin channel catfish; ictalurus punctatus; siluriformes; ictaluridae; oconee river; riparian habitats